Comparative performances of EU-15 and Turkey: a PIN analysis - Karagoz, M. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
Turkey started the accession process with European Union (EU) in 2005. One of the main topics of EU Turkey negotiations was the economic convergence of Turkey to EU norms. This study devises and uses Panel Index Numbers (PIN) analysis to evaluate the performance and convergence prospects of Turkish economy in the face of EU-15 economies. As evaluation areas, we have selected two main macroeconomic indicators as GDP and Export. Our results have shown that, for both indicators, Turkish economy outperforms rest of the EU-15 economies, a point that should be valuable in the process of accession.
Keywords: Performance analysis; accession process; panel data; convergence; C43; C65; C82; REAL CONVERGENCE; POLICY; Business & Economics